Specific enrichment of hyperthermophilic electroactive Archaea from deep-sea hydrothermal vent on electrically conductive support. (July 2018) - Pillot, Guillaume; Frouin, Eléonore; Pasero, Emilie; Godfroy, Anne; Combet-Blanc, Yannick; Davidson, Sylvain; Liebgott, Pierre-Pol
Graphical abstract: Highlights: Development of a new semi-automatic hyperthermophilic bioelectrochemical system. Enrichment of hyperthermophilic exoelectrogen community in MEC system. Specific enrichment of Archaea in MEC system. Potential exoelectrogenic capability of Thermococcus spp. Abstract: While more and more investigations are done to study hyperthermophilic exoelectrogenic communities from environments, none have been performed yet on deep-sea hydrothermal vent. Samples of black smoker chimney from Rainbow site on the Atlantic mid-oceanic ridge have been harvested for enriching exoelectrogens in microbial electrolysis cells under hyperthermophilic (80 °C) condition. Two enrichments were performed in a BioElectrochemical System specially designed: one from direct inoculation of crushed chimney and the other one from inoculation of a pre-cultivation on iron (III) oxide. In both experiments, a current production was observed from 2.4 A/m 2 to 5.8 A/m 2 with a set anode potential of −0.110 V vs Ag/AgCl. Taxonomic affiliation of the exoelectrogen communities obtained on the electrode exhibited a specific enrichment of Archaea belonging to Thermococcales and Archeoglobales orders, even when both inocula were dominated by Bacteria .